QUALITY ASSURANCE IN LEARNING SUPPORT IN DISTANCE EDUCATION SYSTEM: AN EFFORT TO PROVIDE QUALIFIED HIGHER EDUCATION IN INDONESIA - Boromeus, Supartomo Corolus; Malau, Ribut Alam; Andriani, Durri; Hiariey, Lilian Sarah (LPPM Universitas Terbuka, 2013)
Universitas Terbuka, a higher education institution in Indonesia which implements a distance education system with the head office located in Jakarta and 37 regional offices across the country, ensures that all activities have been conducted using quality assurance system. The system adopted from the Indonesia Accreditation Board for Higher Education and the International standard for Distance Education institution. All UTs ROs have got ISO (International Organisation for Standardisation). To ensure that the procedures in ISO have been followed accordingly, monitoring and evaluation have been done in all aspects including face-to-face tutorial. Nevertheless, Ambon RO and Kupang RO face challenges in providing qualified face-to-face tutorials as a result of limited expertise in the areas, limited facilities for face-to-face tutorials, and transportation problems. The analysis of how Ambon RO and Kupang RO implement regulations and procedures on face-to-face tutorial is carried out through document analysis. Data on face-to-face tutorial preparation and implementation in the first and second semester of 2011 for Ambon RO and first semester of 2012 for Kupang RO is analyzed. In general, Ambon and Kupang ROs have managed to follow the procedures required to ensure that they have provided quality face-to-face tutorials for students. Some adjustment have to be taken to accomodate constraints faced. Universitas Terbuka, perguruan tinggi yang menerapkan sistem pendidikan jarak jauh dengan kantor pusat di Jakarta dan 37 Unit Pelaksana Belajar Jarak Jauh UT yang tersebar di seluruh Indonesia, memastikan seluruh kegiatan dilakukan sesuai dengan sistem jaminan mutu yang telah ditetapkan. Sistem jaminan mutu di UT dikembangkan dengan merujuk pada Badan Akreditasi Nasional Perguruan Tinggi dan peraturan dari lembaga internaisonal. UT juga telah mendapatkan ISO. Salah satu aspek penting di UT adalah layanan bantuan belajar untuk mahasiswa dalam bentuk tutorial tatap muka. Tulisan ini menyajikan hasil analisis penanganan tutorial tatap muka di dua UPBJJ UT, Ambon dan Kupang. Mengelola tutorial tatap muka di kepulauan membuat UPBJJ UT Ambon dan Kupang mengalami kendala dalam menunjuk tutor yang kompeten, keterbatasan sarana, dan kesulitan transportasi. Data yang digunakan dalam analisis adalah data persiapan dna pelaksanaan tutorial tatap muka semester 1 dan 2 tahun 2011 di UPBJJ Ambon dan semester 1 di UPBJJ UT Kupang. Data dianalisis secara kualitatif. Hasil analisis menunjukkan bahwa secara umum UPBJJ UT Ambon dan Kupang sudah berhasil melakukan persiapan dan pelaksanaan tutorial tatap muak sesuai dengan prodedur yang ditetapkan. Meskipun demikian dilakukan ditemukan penyesuaian prosedur untuk mengakomodasi kendala yang ada.